Implementing embodied learning in the classroom: effects on children’s memory and language skills - Kosma, Panagiotis; Ioannou, Andri; Zaphiris, Panayiotis (My University, 2019)
The relationship among bodily movements, cognitive abilities, and academic achievement in children is receiving considerable attention in the research community. The embodied learning approach is based on the idea of an inseparable link between body and mind in learning, aiming for teaching methods that promote children’s active engagement in the classroom. This study implements embodied learning as a part of the classroom curriculum in a real classroom environment using motion-based games. A total of 52 elementary students engaged in embodied learning in-class activities for four months. The data-set included standardized pre-post testing for children’s cognitive and academic performance, general learning analytics from games’ usage, interviews, and observations from the teachers involved. Findings showed significant effects both on children’s cognitive abilities (i.e., short-memory skills) and academic performance (i.e., expressive vocabulary). This article contributes to the educational technology community by providing an example of implementing embodied learning via use of motion-based technologies in a real classroom environment.
Keywords: Embodied learning; Embodied cognition (EC); Motion-based technologies; Movement; Classroom